Visualizing Genotypic and Developmental Differences of Free Amino Acids in Maize Roots With Mass Spectrometry Imaging - O’Neill, Kelly C.; Lee, Young Jin (Frontiers in Plant Science, 2020)
Amino acids are essential biological compounds in plants as they store nitrogen, an essential nutrient, and are the building blocks for proteins that drive biological activity. Amino acids have been studied using a wide variety of analytical techniques in different plant systems, however, mass spectrometry imaging (MSI) is a particularly useful technique as it allows for the simultaneous collection of both chemical and spatial information. In this work, matrix-assisted laser desorption/ionization (MALDI)-MSI is used to study the different localization of free amino acids in the roots of maize inbred lines B73 and Mo17 and their reciprocal hybrids. Because amino acids are difficult to detect in mass spectrometry, especially directly on tissues, a chemical derivatization protocol is utilized to increase the ionization efficiency and improve their detection. We report differences in both abundance and localization of amino acids in B73 and Mo17 maize roots and suggest the hybrids show evidence of inheriting characteristics from both parents. Most genotypic differences are found in the cross-sections near the seed (∼2 cm away) at a later stage of development (10–11 cm in length). Here, B73 has lower amino acid abundance localized primarily to the center of the roots for most amino acids, while Mo17 has much higher abundance localized mainly to the root cortex. This difference in localization is minimized when grown in ammonium ion rich conditions. Roots grown in the presence of 15N-ammonium ions provided additional insight about the amino acid synthesis. The localization of some amino acids, particularly leucine/isoleucine and glutamine, is not affected by the addition of nitrogen and is consistent regardless of the nitrogen source, either from the seeds (14N-labeled) or environment (15N-labeled). Nitrogen uptake from the environment is confined to glutamine, asparagine, and alanine, consistent with their roles in amino acid storage and transportation.